Factors influencing cervical cancer re-screening in a semi-rural health district of Cameroon: a cohort study - Sophie Evina Bolo; Bruno Kenfack; Ania Wisniak; Gilles Tankeu; Virginie Yakam; Alida Moukam; Jessica Sormani; Beat Stoll; Pierre Vassilakos; Patrick Petignat (BMC Women's Health, 2024)
Abstract Background Screening participation at recommended intervals is a crucial component of cervical cancer prevention effectiveness. However, little is known regarding the rate of re-screening in a Sub-Saharan context. This study aimed to estimate the re-screening rate of women in a semi-rural after an initial HPV-based screening and identify factors that influence adherence. Methods This cohort study at the Annex Regional Hospital of Dschang enrolled women screened for cervical cancer over 5 years ago and due for re-screening. Women who initially tested HPV-positive (n = 132) and a random sample of HPV-negative women (n = 220) participated in a telephone survey between October 2021 and March 2022 to assess re-screening participation and reasons. Sociodemographic factors were collected, and associations with rescreening were evaluated. Results A total of 352 participants aged under 50 years (mean age 37.4 years) were contacted, and 203 (58.0%) completed the survey. The proportion of women who complied with the screening recommendation was 34.0% (95% CI 27.5% − 40.5%), The weighted re-screening proportion was 28.4%. Age, marital status, education level, type of employment, and place of residence were not associated with the rate of re-screening. Main reported barriers to re-screening were lack of information (39.0%), forgetfulness (39.0%), and impression of being in good health (30.0%). Women who remembered the recommended screening interval were 2 to 3 times more likely to undergo re-screening (aOR (adjusted odds ratio) = 2.3 [1.2–4.4], p = 0.013). Human papilloma virus- positive status at the initial screening was also associated with the re-screening((aOR) (95% CI): 3.4 (1.8–6.5). Conclusion Following an initial Human Papilloma Virus-based screening campaign in the West Region of Cameroon, one third of women adhered to re-screening within the recommended timeframe. Existing screening strategies would benefit from developing better information approaches to reinforce the importance of repeated cervical cancer screening.